The effect of the social and interpersonal-based intervention on calcium consumption among pregnant women - Heidari, Neda; Amiri, Masoomeh; Rajati, Fatemeh; Mahaki, Behzad; Rajati, Mojgan (Frontiers in Public Health, 2025)
IntroductionThe present study aimed to evaluate the effect of educational intervention based on Pender’s health promotion model on the calcium intake of pregnant women.MethodsThe pregnant women at three to 5 months were recruited using convenient sampling method and randomly assigned either to the control (n = 37) or intervention (n = 36) groups referred to the health centers in Kermanshah, “Iran,” in 2022, 2023. Participants were randomly assigned to either the intervention group or the control group. The intervention consisted of a series of educational workshops that provided information on the importance of calcium, dietary sources, and practical methods for increasing calcium intake. Participants received personalized dietary plans, and improve knowledge, perceived benefits of action, perceived barriers to action, perceived self-efficacy, activity-related affect, interpersonal influences, situational influences, immediate competing demands and preferences, commitment to plan of action and over 8-week period, and ongoing support through one-month follow-up. The control group received standard prenatal care without additional nutritional education. Pre- and post-intervention assessments measured calcium intake and HPM constructs using validated questionnaires. The food frequency questionnaire was completed before and after the intervention. Data were analyzed in SPSS software version 25.ResultsThere is no significant difference between the intervention and control groups at baseline (p < 0.05). According to the independent sample t-test, all constructs of the Pender’s HPM except for interpersonal influences were significantly improved in the intervention rather than control groups (p > 0.05). The repeated measure ANOVA demonstrated a significant difference in the effect of the intervention on the constructs of the knowledge (F = 9.40; p-value = 0.001), perceived benefits (F = 17.24; p-value = 0.001), perceived barriers (F = 40.80; p-value = 0.001), perceived self-efficacy (F = 10.90; p-value = 0.001), activity-related affect (F = 14.85; p-value = 0.001), interpersonal influences (F = 21.51; p-value = 0.001), commitment to a plan of action (F = 20.20; p-value = 0.001), and immediate competing demands and preferences (F = 9.4; p-value = 0.001) between the intervention and control groups. The ANOVA demonstrated that the calcium consumption significantly increased in the intervention group (p < 0.001).DiscussionA theory-based educational intervention in the health care system can fill the gap in the successful implementation of nutrition education programs.